Health Education Audiovisual Media on Mental Illness for Family - Dyah Wahyuningsih; Ruti Wiyati; Widyo Subagyo (Poltekkes Kemenkes Semarang, 2012)
This study aimed to produce health education media in form of Video Compact Disk (VCD). The first disk consist of method how to take care of patient with social isolation and the second disk consist of method how to take care of patient with violence behaviour. The implementation of audiovisual media is giving for family in Psyciatric Ward Banyumas hospital. The family divided in two groups, the first group was given health education about social isolation and the second group was given health education about violence behaviour. Analizise method used frequency distribution and the family respon with question. The implementation of this media showed that after giving family education, the family knowledge about caring patient with social isolation and violence behaviour was increased.